Fabrication of chitosan-flax composites with differing molecular weights and its effect on mechanical properties. (12th April 2023) - Rath, Amrita; Grisin, Benjamin; Pallicity, Tarkes Dora; Glaser, Lukas; Guhathakurta, Jajnabalkya; Oehlsen, Nina; Simon, Sven; Carosella, Stefan; Middendorf, Peter; Stegbauer, Linus
Abstract: An aqueous fabrication method is investigated for a composite reinforced with chitosan and flax fibers. The composite is characterized structurally, mechanically and chemically. A strong influence of molecular weight (MW) is identified on the composite properties. A strong fiber-matrix interface, which is associated with porosity and effective fiber impregnation, is achieved by applying low molecular weight (LMW) solution followed by casting using LMW or medium molecular weight (MMW) solution. Porosity is analyzed using μ-CT analysis. Increasing porosity with increasing molecular weight results in a decline of the tensile and flexural properties of the composites. The chitosan-flax composites have a low density compared to synthetic and natural fiber composites, which is a competitive advantage as a replacement material for particle board or plyboard in suspended ceilings, furniture compartments, sports or leisure equipment. A multiscale simulation is carried out to compute the directional effective elastic properties and predicts a potential 21% improvement of the tensile modulus if the process is optimized. This work shows the potential of chitosan-flax composites as a sustainable green material with an aqueous fabrication procedure and useful mechanical properties. Graphical abstract: Image 1